1992
DOI: 10.1007/bf02536482
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipids of a human glioma cell line bearing receptors for platelet‐derived growth factor (PDGF)

Abstract: Glycolipids of U-1242 MG were characterized because results of previous studies showed that exogenous gangliosides, especially GM3, inhibit PDGF-stimulated growth of this human glioma cell line. GM3 and GM2 are the major gangliosides; both separate as doublets with thin-layer chromatography. The major neutral glycolipid is glucocerebroside with nonhydroxy fatty acids, but paragloboside, ceramide dihexoside, globoside, and asialoGM2 (GA2) are also present. The coexistence in U-1242 MG of these gangliosides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…We previously established a modified tetracyclineregulatable (Tet On) system controlling GD3 synthase gene expression [10] in the GD3-deficient glioma cell line U-1242 MG [11]. We found that the transfected cell line, U1242MG-GD3, responds to doxycycline by increasing its synthesis of GD3.…”
Section: Introductionmentioning
confidence: 98%
“…We previously established a modified tetracyclineregulatable (Tet On) system controlling GD3 synthase gene expression [10] in the GD3-deficient glioma cell line U-1242 MG [11]. We found that the transfected cell line, U1242MG-GD3, responds to doxycycline by increasing its synthesis of GD3.…”
Section: Introductionmentioning
confidence: 98%
“…The most complex form of glycosphingolipids are gangliosides, which are characterized by a variable number of negatively charged sialic acid residues attached to hydrophilic sugar moieties. Gangliosides have been shown to play roles in a number of cellular functions, including cell recognition and adhesion (1-3), signal transduction (3), and cell growth regulation (4,5). Although a minor component in most cells, they constitute up to 10% of the total lipid mass in nerve cells (6).…”
Section: Introductionmentioning
confidence: 99%
“…The most complex form of glycolipids are gangliosides, which contain one or more negatively charged sialic acid groups. Gangliosides are thought to play roles in a number of cellular functions, including cell recognition and adhesion (1)(2)(3), signal transduction (3), and cell growth regulation (4). Although a minor component in most cells, they constitute 5-10% of the total lipid mass in nerve cells (5), and because they reside primarily on the outer leaflet of the cell membrane, the external surfaces of certain cells contain 10-20 mol % ganglioside.…”
Section: Introductionmentioning
confidence: 99%